2019
DOI: 10.7759/cureus.6113
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Liver Lobe Attached to the Wall of the Gallbladder

Abstract: A 47-year-old woman with a history of known gallstone disease presented with worsening post-prandial right upper abdominal pain radiating to the back, abdominal bloating, and nausea. An ultrasound of the abdomen confirmed the diagnosis of cholelithiasis. During laparoscopic cholecystectomy, an accessory liver lobe attached to the anterior wall of the gallbladder was incidentally found. An accessory liver lobe is a rare anatomical variation that mostly remains clinically asymptomatic. Since hepatocellular carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Pathological findings previously demonstrated that ALL contains three major structures: a portal vein, hepatic artery, and bile ducts [ 8 , 9 ]. Vessels and bile ducts in ALL (particularly pedunculated lobes) may be connected to the main liver.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological findings previously demonstrated that ALL contains three major structures: a portal vein, hepatic artery, and bile ducts [ 8 , 9 ]. Vessels and bile ducts in ALL (particularly pedunculated lobes) may be connected to the main liver.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography, plain CT scan, and MRI have also been reported to be non-specific for diagnostic imaging findings in pediatric AHL patients ( 5 ). Hepatic infarcts often showed as hypoechoic, non-vascular areas on ultrasonography ( 15 ). The typical AHL demonstrated on CT is a mass with a narrow base or broad bottom attached to the healthy liver, with the Hounsfield unit consistent with healthy liver tissue ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the previously vascularized lobe infarcts, some of its imaging characteristics lose their similarity to the normal appearing adjacent liver. The ultrasound findings of a liver infarct are represented as hypoechoic, nonvascular regions on conventional and Doppler sonography [11] . Similarly, the “mass” seen in our patient was originally described as a heterogeneously hypoechoic (relative to normal liver parenchyma) and echogenic masslike structure without flow on color Doppler which lead to the initial diagnosis of a hematoma.…”
Section: Discussionmentioning
confidence: 99%